Molecular diagnosis in mitochondrial complex I deficiency using exome sequencing. Issue 4 (12th April 2012) - Haack, Tobias B; Haberberger, Birgit; Frisch, Eva-Maria; Wieland, Thomas; Iuso, Arcangela; Gorza, Matteo; Strecker, Valentina; Graf, Elisabeth; Mayr, Johannes A; Herberg, Ulrike; Hennermann, Julia B; Klopstock, Thomas; et al.
Abstract : Background: Next generation sequencing has become the core technology for gene discovery in rare inherited disorders. However, the interpretation of the numerous sequence variants identified remains challenging. We assessed the application of exome sequencing for diagnostics in complex I deficiency, a disease with vast genetic heterogeneity. Methods: Ten unrelated individuals with complex I deficiency were selected for exome sequencing and sequential bioinformatic filtering. Cellular rescue experiments were performed to verify pathogenicity of novel disease alleles. Results: The first filter criterion was 'Presence of known pathogenic complex I deficiency variants'. This revealed homozygous mutations in NDUFS3 and ACAD9 in two individuals. A second criterion was 'Presence of two novel potentially pathogenic variants in a structural gene of complex I', which discovered rare variants in NDUFS8 in two unrelated individuals and in NDUFB3 in a third. Expression of wild-type cDNA in mutant cell lines rescued complex I activity and assembly, thus providing a functional validation of their pathogenicity. Using the third criterion 'Presence of two potentially pathogenic variants in a gene encoding a mitochondrial protein', loss-of-function mutations in MTFMT were discovered in two patients. In three patients the molecular genetic correlate remained unclear and follow-up analysis is ongoing. Conclusion: Appropriate in silico filtering of exome sequencing data, coupled with functional validation of new disease alleles, is effective in rapidly identifying disease-causative variants in known and new complex I associated disease genes.